Antitumor Activity in vitro by 9-Oxo-10,11-dehydroageraphorone Extracted from Eupatorium adenophorum - Liao, Fei; Hu, Yanchun; Wu, Lei; Tan, Hui; Mo, Quan; Luo, Biao; He, Yajun; Deng, Junliang; Wei, Yahui (Asian Journal of Chemistry, 2014)
Ultrasonic-methanol extraction was used to extract cadenine sesquiterpene from Eupatorium adenophorum and then the crude 9-oxo-10,11-dehydroageraphorone (euptox A) was purified by column chromatography and XAD-2 Macroporous Resin. 4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to test the cytotoxicity of euptox A to human lung cancer A549 cells, Hela cells and Hep-2 cells in vitro. The results suggest that euptox A had significant antitumor activity against the three tumor cell lines in vitro in a dose-dependent manner. When the concentration of euptox A was at 500 μg/mL, the percent inhibition of human lung cancer A549 cells, Hela cells and Hep-2 cells were 76.42, 68.30 and 79.05 %, respectively. The 50 % inhibitory concentration (IC50) of euptox A for the three tumor cell lines were 369, 401 and 427 μg/mL (A549, Hela and Hep-2 cells, respectively). The results suggest it's better than the control of the 5-FU and euptox A may be considered as a potential candidate for developing a novel low toxicity antitumor agent.